Leveraging social media as avenues for da'wah among Muslim youths in Nigeria - Abana, Amina (Islamic Communication Journal, 2025)
This paper reviews the usage and impact of social media in the society and how they can be leveraged for da'wah by youths in Nigeria. It explores the various meanings, uses and impacts of social media; and identified some of the advantages and disadvantages of social media on people and societies. The paper further examined literature and empirical data from scholars on da’wah, social media, and the usage of social media for da'wah and other Islamic propagation. Data revealed that social media have been used effectively for da'wah but can also be used to disseminate messages of dissent. However, this paper argues that since a significant portion of Nigeria’s population are Muslims and youths constitute the major users of social media; leveraging social media platforms for da'wah can be an effective way for Muslims youths to fulfil their religious duty by sharing Islamic teachings and values with others; reach wide audience and help in correcting misconception about Islam and Muslims. Hence, this paper clarified concepts, identified best practices, and contributed to a deeper understanding of Islamic communication in the age of digital media, particularly by providing insights and strategies on developing da’wah initiatives using different social media platforms. ***** Artikel ini mengulas penggunaan dan dampak media sosial dalam masyarakat dan bagaimana media sosial dapat dimanfaatkan untuk da'wah oleh kaum muda di Nigeria. Studi ini menggunakan pendekatan literatur dengan berfokus pada pemikiran para sarjana tentang dakwah, media sosial, dan penggunaan media sosial untuk dakwah dan penyebaran Islam, dan juga menggunakan beberapa data empiris dalam konteks Nigeria. Data mengungkapkan bahwa media sosial telah digunakan secara efektif untuk dakwah tetapi juga dapat digunakan untuk menyebarkan pesan perbedaan pendapat. Namun, makalah ini berpendapat bahwa karena sebagian besar penduduk Nigeria adalah Muslim dan kaum muda merupakan pengguna utama media sosial; memanfaatkan platform media sosial untuk dakwah dapat menjadi cara yang efektif bagi kaum muda Muslim untuk memenuhi kewajiban agama mereka dengan berbagi ajaran dan nilai-nilai Islam dengan orang lain; menjangkau khalayak luas dan membantu dalam mengoreksi kesalahpahaman tentang Islam dan Muslim. Oleh karena itu, penelitian ini mengklarifikasi konsep, mengidentifikasi praktik terbaik, dan berkontribusi pada pemahaman yang lebih dalam tentang komunikasi Islam di era media digital, khususnya dengan memberikan wawasan dan strategi dalam mengembangkan inisiatif da’wah menggunakan berbagai platform media sosial.